(untitled) (Journal of Informatics Education and Research, 2025)
Electronic equipment aimed at end users has evolved into a staple of daily life. Conventional approaches have undergone significant alteration, resulting in effective communication channel and quick information retrieval. Sales, storage, destruction, and then collection patterns have all changed as a result of the exponential growth in demand and output. This essay examines a variety of these practices in (electronic) waste management and suggests remedies including recycling management and other rules and regulations that must be adhered to. Authors have placed a strong emphasis on offering comprehensive information that might be helpful to the regulatory agencies in charge of waste management or the producers of different electronic devices, as well as the policy makers. Using a thorough examination of electronic waste, authors have highlighted three factors (sales, storage and its destruction). Electronic equipment geared towards end users has evolved into a staple of daily life. Conventional approaches have radically changed, resulting in effective behaviors for managing (electronic) waste and recommending remedies like recycling management, various directions, and laws that must be adhered to. Authors have placed a strong emphasis on offering comprehensive information that might be helpful to the regulatory agencies in charge of E- waste managing or the manufacturers of different electronic devices, as well as the policy makers.